Relationship Between The Postpartum Servical Smear and The Delivery Route: Vaginal or Cesarean - Eryılmaz, Özlem Gün; Yılmaz, Saynur; Özler, Sibel; Gülerman, Cavidan (Fırat University, 2013)
Objective: The postpartum period, just like pregnancy, during which the patient is in frequent contact with health care personnel, provides an invaluable opportunity for cervical screening. While vaginal birth is reported to have a clearing effect on preexisting cervical lesions, some studies suggest that when compared to deliveries by caesarean section vaginal delivery has no obvious benefits on cervical lesions. In this study we aimed to investigate the effects of delivery routes, vaginal or caesarean section, on cervical smear results. Material and Method: In this retrospective case control study, a total of 48 patients with vaginal delivery were compared to 48 deliveries by cesarean route with respect to age, gravidity, parity, history of dilatation and curettage, neonatal birth weight, postpartum maternal complaints and results of postpartum cervical smears. Results: Postpartum maternal complaints were significantly higher with vaginal deliveries when compared to the cesarean group, p=0.0001. Among these complaints, reported dyspareunia was higher in the vaginal delivery group when compared to the cesarean group, p=0.0007. The results of the postpartum cervical smears were similar between the groups, p>0.05. None of the smear results showed low or high grade cervical intraepithelial neoplasia. Conclusion: In this study based on the evaluation of postpartum cervical smear results, cervical effects of vaginal and caesarean deliveries were found to be the same and vaginal delivery was not shown to offer benefits in terms of cervical healing when compared to delivery by caesarean section.

Amaç: Postpartum dönem, tıpkı gebelik dönemi gibi, hastanın sağlık personeli ile sık irtibat kurduğu, servikal tarama için kaçırılmayacak bir süreçtir. Vajinal doğumun, servikste var olan lezyonları giderici etkiye sahip olduğu söylenirken, sezaryene oranla etkisinin olmadığı da ifade edilmektedir. Bu çalışmada, doğum şeklinin, postpartum servilak yayma sonuçlarına etkisini belirlemeye çalıştık. Gereç ve Yöntem: Retrospektif vaka kontrol yöntemi ile gerçekleştirilen bu çalışmada, toplam 48 vajinal doğum yapmış hasta, yine 48 sezaryen ile doğum yapmış hasta ile yaş, gravida, parite, geçirilmiş küretaj sayısı, bebek doğum ağırlığı, postpartum maternal şikayetler ve postpartum servikal yayma sonuçları açısından karşılaştırıldı. Bulgular: Postpartum maternal şikayetler, vajinal doğum grubunda, sezaryen grubuna oranla, istatistiksel olarak daha fazla tespit edildi (p=0.0001), bunların içinde disparöni, vajinal doğum sonrası, sezaryene oranla anlamlı olarak daha sık ifade edildi, p=0.0007. Gruplar arasındaki, servikal yayma değerlendirme sonuçları benzer çıktı, p>0.05. Hiçbir hastada, düşük yada yüksek dereceli servikal neoplazi tespit edilmedi. Sonuç: Postpartum servikal yayma sonuçları incelenerek yapılan bu çalışmada, doğumun vajinal veya sezaryen ile gerçekleşmesinin, serviksi aynı şekilde etkilediğini, vajinal doğumun, serviksteki hücresel iyileşmelerde, sezaryenden daha üstün olmadığını belirledik.
Vajinal ve Sezaryen Doğumun Postpartum Servikal Yayma Sonuçlarına Etkisi